CHARACTER EDUCATION CHARACTER EDUCATION IN THE NOVEL OF DREAMS OF KIDS ISLANDS ABIDAH EL KHALIEQY - Amiruddin Amiruddin; Muhammad Thohir Nst (Universitas Dharmawangsa, 2020)
This study aims to know clearly about the values of character education in the novel Island Dream Child. The method used is descriptive method means that the data obtained, analyzed, and described using words or phrases not in the form of numbers or use calculations. Results of the data analysis resulted in the conclusion that the concept of character education in the novel Dream Child Island includes several values which are: the value of honest (honest in answering questions, be honest to yourself and God, honest to themselves and parents, honestly admit shortcomings, honest opinion, and honestly admit mistakes). The value of responsibility (family responsibilities, responsibilities towards God, and responsibility to the job). Value intelligent (smart in calculating, smart in answering questions, intelligent in thought, and intelligent have an idea). The value of care (social care).